Spiritualizing Adversity Quotient through Islamic Values: A Phenomenological Study of Bullying Mitigation in Muhammadiyah Secondary Schools - Sutarman; Kurniawan, Muhammad Ragil; Parjiman; Sutrisno; Hakim, Ahmad Luqman; Murtono (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose — In the context of the dominance of secular paradigms, this study reconstructs the Adversity Quotient (AQ) by integrating Islamic spiritual anchors Sabar, Tawakkal, and Ukhuwah as a spiritual foundation shaping students’ responses to adversity. Using a phenomenological perspective, the research examines how faith-based values are experienced and interpreted in Muhammadiyah secondary schools in relation to bullying. Design/methods/approach — This research used a qualitative approach by synergizing Interpretive Phenomenological Analysis (IPA) with the Miles, Huberman, and Saldana (MHS) framework. IPA was used because of its idiographic depth to capture the double hermeneutic of students’ spiritual resilience, while the MHS framework upheld procedural sharpness through data condensation and systematic pattern verification. Data were collected from nine purposive informants at SMA Muhammadiyah Imogiri, Yogyakarta, through in-depth interviews and observations, ensuring a balanced synthesis between individual life experiences and structured thematic findings. Findings — The findings indicate that the internalization of Islamic character values and adversity quotient functions as an existential anchor, enabling students to reinterpret challenges as opportunities for spiritual growth. This meaning-making process strengthens students’ AQ and supports restrained responses to bullying by framing conflict as spiritual testing (ibadah). However, students with disabilities continued to experience vulnerabilities in school social relations, reflecting differing horizons of meaning among student groups. Research implications/limitations – By foregrounding subjective meaning and lived experience, this study contributes to Islamic education discourse through a value-oriented interpretive framework. The findings are limited to Islamic school contexts and do not fully represent experiences in general schools or those of students with disabilities. Originality/value – This study bridges Islamic spiritual values with AQ dimensions, positioning faith-based practices as interpretive resources supporting students’ resilience in responding to bullying.